BioFlx smiles: aesthetic rehabilitation of primary anterior teeth using bioflx crowns - a case report - A. V., Saisree; Mallappa, Jamkhandi S.; Pai, K. Reshma; Pallavi K., Lakshmi; Bhat, Ananthakrishna; Dsouza , Evette N. (International Journal of Contemporary Pediatrics, 2025)
Restoring primary anterior teeth poses a unique challenge in pediatric dentistry, requiring a balance between function, esthetics, and durability. BioFlx crowns, an innovative alternative to traditional zirconia and composite crowns, offer enhanced flexural strength, biocompatibility, with a consistent appearance that ensures reliable esthetic outcomes. This case report presents the rehabilitation of maxillary primary central and lateral incisors (teeth 51, 52, 61, and 62) using BioFlx crowns in a young child. The treatment approach, including case selection, crown adaptation, and clinical outcomes, is discussed. The patient exhibited significant aesthetic and functional improvement, with high parental satisfaction. BioFlx crowns demonstrate promising potential as a reliable and aesthetically pleasing restorative option for anterior pediatric dental rehabilitation.